Revisiting EKC hypothesis in context of renewable energy, human development and moderating role of technological innovations in E-7 countries? - Saqib, Najia; Usman, Muhammad; Radulescu, Magdalena; Sinisi, Crenguta Ileana; Secara, Carmen Gabriela; Tolea, Claudia (Frontiers in Environmental Science, 2022)
The present study examines the potential of the traditional environmental Kuznets curve (EKC) with an extension for growing industrialized economies, including Brazil, China, India, Indonesia, Russia, Mexico and Turkey (E-7 economies) spanning from 1995 to 2019. Since the E-7 economies are still in a growing phase, this study adds to the EKC phenomenon by taking into description human development, the use of renewable energy, and technological innovations for investigation. Second-generational panel econometrics techniques, such as cross-sectional augmented autoregressive distributive lag (CS-ARDL), Augmented Mean Group (AMG), and Dumitrescu-Hurlin causality tests, form the basis of the experimental framework’s design. The study confirms the existence of the EKC phenomena in E-7 economies, where income expansion is prioritized in relation to environmental sustainability. The study’s findings demonstrate that technological modernization helps to mitigate pollution level. Therefore, human development, technological innovation, and the use of renewable energy are held up as the panacea for reducing carbon emissions over the time period under study. Finally, some further policy suggestions are provided.